2014
DOI: 10.1155/2014/269681
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Sepsis and Inflammatory Mediators

Abstract: Neonatal sepsis is a major cause of morbidity and mortality and its signs and symptoms are nonspecific, which makes the diagnosis difficult. The routinely used laboratory tests are not effective methods of analysis, as they are extremely nonspecific and often cause inappropriate use of antibiotics. Sepsis is the result of an infection associated with a systemic inflammatory response with production and release of a wide range of inflammatory mediators. Cytokines are potent inflammatory mediators and their seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
97
2
34

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(137 citation statements)
references
References 116 publications
(132 reference statements)
4
97
2
34
Order By: Relevance
“…Interleukin-6 and tumor necrosis factor- Interleukin-6 (IL-6) and Tumor necrosis factor- (TNF-) are two cytokines that are known to mediate changes in musculoskeletal and immune systems. 4 They are pro-inflammatory cytokines that mediate process of inflammation and healing. However when released in excess, they can cause unwanted exacerbation of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin-6 and tumor necrosis factor- Interleukin-6 (IL-6) and Tumor necrosis factor- (TNF-) are two cytokines that are known to mediate changes in musculoskeletal and immune systems. 4 They are pro-inflammatory cytokines that mediate process of inflammation and healing. However when released in excess, they can cause unwanted exacerbation of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory responses are necessary for the host to respond to components of invading organisms. At the early stages of infection, TNF-α, IL-1β, IL-6, and IL-8 pro-inflammatory cytokines are produced and stimulate immune cells leading to activation of an inflammatory cascade (47). The subsequent inflammatory cascade includes many biologically active mediators and can induce a systemic inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response is thereafter counteracted by anti-inflammatory mediators to restore immunological homeostasis. Excessive pro-inflammatory mediators or inadequate anti-inflammatory responses will lead to sepsis (47). In addition to antibiotics, other adjuvant therapies primarily target the dysregulated innate immune response.…”
Section: Discussionmentioning
confidence: 99%
“…While the VV ECMO patients had higher serum creatinine levels (Table 1), post-hoc analyses demonstrated no direct correlation between serum creatinine and either GM or WM creatine (data not shown). On the other hand, systemic inflammation (e.g., elevated c-reactive protein, elevated pro-inflammatory cytokines) has been documented in neonates with ECMO [30, 31], as well as in neonates with clinical sepsis [32] and studies have demonstrated that creatine is often elevated alongside choline in the setting of cerebral inflammation [25, 27]. Taken together, the elevations in creatine and choline suggest that the systemic inflammatory response could extend to the central nervous system, as demonstrated in animal models [33].…”
Section: Discussionmentioning
confidence: 99%